Has LRRP Moved The Needle? Examining the Effectiveness of EPA's 2010 Lead Renovation, Repair & Painting Rule - Higgins, Jeffrey. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Economics.; Advisor: Ujjayant Chakravorty.; Committee: Jeffrey Zabel.; Keyword: Economics.; Though cases of severe lead poisoning in children have fallen dramatically in the U.S. since the mid-20th century, the contemporary medical literature has established that lead is still toxic at low levels of exposure (Lanphear 2007; NTP 2012; ATSDR 2019). In April 2010, EPA implemented the Lead Renovation, Repair, and Painting Rule (LRRP) (EPA 2011; EPA 2019), which requires renovators disturbing lead-based paint in residential homes and child-occupied facilities to attain certification and use best-practice cleaning and containment methods. I exploit time series variation in lead poisoning outcomes to estimate the efficacy of LRRP, employing regression discontinuity design with time as the running variable. I find LRRP had a small impact, reducing mild cases of lead poisoning (blood-lead level>10 µg/dL) by 0.87% and more severe cases of lead poisoning (blood-lead level>25 µg/dL) by 0.06%. However, these results appear to be carried by states without robust state-level lead programs. I evaluate heterogeneity in the treatment effect, comparing the effect of LRRP in states with and without a state-level lead abatement program. I find there were 1.16% more mild cases and 0.12% more severe cases in states with a lead abatement program compared to states without one.